Analisis Implementasi Aliran Progresivisme Dalam Pembelajaran: Tinjauan Terhadap Praktik Pengajaran Seorang Guru (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This research aims to understand the concept of progressivism and explore in depth how a teacher implements progressivism in his teaching practice. Along with changes in social and technological dynamics, learning is no longer simplified to merely transferring information but students also play an active role in learning activities. Research conducted using interviews is a type of qualitative research, which aims to understand a particular phenomenon or context through collecting and analyzing non-numerical data, such as text, images or sound. The subject of this research was a teacher at SMP Negeri 1 Sidamanik, named Hermaulina Siallagan, S.Pd and also the answers to the questions given. Researchers conducted online interviews with sources via Google Meet or the Gmail application. The results of the research show the implementation of progressivism in Mrs. Hermaulina's teaching practice, namely that she defines a teacher as an educator and teacher. In terms of learning carried out by Mrs. Hermaulina, she focuses more on student-centred learning. Then he also prioritizes collaborative learning, both collaboration between teachers and students and collaboration between students and other students. Thus, Mrs. Hermaulina has implemented the flow of progressivism in her teaching practice.